2022
DOI: 10.1039/d2ra05827h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ca(OH)2 and Na2CO3 through anion exchange between CaCO3 and NaOH: effect of reaction temperature

Abstract: The chemical decarbonisation of CaCO3 was successfully tested in a range of mild temperatures simulating those oscillations occurring within processes, and the kinetic parameters were gained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In those studies, alkaline solutions such as NaOH and KOH tended to have higher concentrations. 9–12 Kojima et al concluded that a suitable amount of alkaline reagent for obtaining Ca(OH) 2 from gypsum was a OH/Ca ratio greater than 2.6. 12 In the present study, we focused on recovering unused alkaline wastewater at lower concentrations and on establishing the optimal pH for obtaining Ca(OH) 2 from gypsum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In those studies, alkaline solutions such as NaOH and KOH tended to have higher concentrations. 9–12 Kojima et al concluded that a suitable amount of alkaline reagent for obtaining Ca(OH) 2 from gypsum was a OH/Ca ratio greater than 2.6. 12 In the present study, we focused on recovering unused alkaline wastewater at lower concentrations and on establishing the optimal pH for obtaining Ca(OH) 2 from gypsum.…”
Section: Resultsmentioning
confidence: 99%
“…This technique does not generate CO 2 gas, yielding sodium carbonate as a useful chemical instead. [9][10][11] Another approach for obtaining Ca(OH) 2 is the treatment of gypsum with aqueous NaOH or potassium hydroxide (KOH). [12][13][14] These techniques exploit the different solubilities of CaCO 3 , gypsum, and Ca(OH) 2 and proceed in accordance with reactions (2)-( 4):…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction is an example of a double displacement reaction, also known as a metathesis reaction. In this type of reaction, the cations and anions switch between two reactants to form new products (Simoni et al 2022).…”
Section: Effect Of Alkaline Pretreatmentmentioning
confidence: 99%